ON HOLISTIC WISDOM CORE DATUM ACCOUNTING: SHIFTING FROM ACCOUNTING INCOME TO VALUE ADDED ACCOUNTING - Mulawarman, Aji Dedi (Accounting Department,, 2014)
This article is designed to create value added accounting concept based on holistic wisdom as supplant of income concept based on conventional accounting. The methodology used is The General Theory of Science from Hidayat Nataatmadja to build a value added concept with harmonious parity, kewargaan (citizenship) and iman (faith). Step one is to detect how accounting is used for Neoliberalism despotism tools that do not match harmonious parity. This is an agenda to enable MNCs (Multi National Companies) to â€œjailâ€ accounting, therefore accounting must be limited-holders orientation designed and formed in conventional financial statement structures. In addition, there is a power need from accounting politics, which are the IAI and national-international networks. For deep interaction analysis, theoretical and political designs are needed to investigate income concept and advanced development from social and environmental accounting approach. Step two, using harmonious citizenship to develop accounting income concept that is free from Neoliberalism clutch, value added concept is employed. However, value-added concept needs to move further towards value added accounting based on holistic wisdom. The result, value added accounting has twelve chakra(s). Accounting does not just take sides to limited-holders, but must also take sides to broadening stakeholders, pro people and environment with God Consciousness based on harmonious iman. This is called holistic holders. Â Key Words: neoliberalism, limited-holders, holistic-holders, value added with holistic wisdom, knowledge of universe, faith-parity-citizenship concordance.